2017
DOI: 10.1002/jsfa.8576
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary resveratrol supplementation on meat quality, muscle antioxidative capacity and mitochondrial biogenesis of broilers

Abstract: Resveratrol can be used as a feed additive to improve meat quality of broilers, which may be associated with improved muscle antioxidative status and mitochondrial biogenesis. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 32 publications
4
38
0
Order By: Relevance
“…The reaction was performed in a final volume of 20 μL, consisting of 10 μL 2 × SYBR Green Fast qPCR Mix with Low Rox, 0.4 μL reverse primers (10 mmol L −1 ), 0.4 μL forward primers (10 mmol L −1 ), 8.8 μL doubled‐distilled water and 0.4 μL cDNA template. The thermal cycler parameters were as follows: 95 °C for 2 min, 40 cycles of 95 °C for 15 s, and 60 °C for 30 s. The melting curve conditions were as follows: 1 cycle at 95 °C for 5 s, 60 °C for 60 s, and 95 °C for 15 s. The mRNA expression levels of target genes were calculated using the 2 −ΔΔCt method and normalized to the mRNA level of β‐actin …”
Section: Methodsmentioning
confidence: 99%
“…The reaction was performed in a final volume of 20 μL, consisting of 10 μL 2 × SYBR Green Fast qPCR Mix with Low Rox, 0.4 μL reverse primers (10 mmol L −1 ), 0.4 μL forward primers (10 mmol L −1 ), 8.8 μL doubled‐distilled water and 0.4 μL cDNA template. The thermal cycler parameters were as follows: 95 °C for 2 min, 40 cycles of 95 °C for 15 s, and 60 °C for 30 s. The melting curve conditions were as follows: 1 cycle at 95 °C for 5 s, 60 °C for 60 s, and 95 °C for 15 s. The mRNA expression levels of target genes were calculated using the 2 −ΔΔCt method and normalized to the mRNA level of β‐actin …”
Section: Methodsmentioning
confidence: 99%
“…The PCR mixture consisted of 10 μL of SYBR Premix Ex Taq ll (Tli RNaseH Plus), 1 μL of each primer, 2 μL of cDNA sample, and 6 μL ddH 2 O. The PCR cycling parameters were in accordance with our previous study . The target gene mRNA expression level was calculated according to the 2 − ΔΔ Ct method, and the β‐actin gene was used as the internal standard.…”
Section: Methodsmentioning
confidence: 99%
“…The PCR cycling parameters were in accordance with our previous study. 26 The target gene mRNA expression level was calculated according to the 2 −ΔΔCt method, 27 and the -actin gene was used as the internal standard.…”
Section: Real-time Pcr Analysismentioning
confidence: 99%
“…RSV has been studied in both animals and humans, and is associated with a wide range of biological effects and cellular pathways. Amongst its properties, it has been shown that RSV acts as an anti-inflammatory [ 125 ], anti-oxidant [ 126 ], anti-diabetic [ 127 ], as well as an osteoprotective agent [ 128 , 129 ] and exercise mimetic [ 129 , 130 ], making it an exceptional candidate to help mitigate muscle deconditioning in our partial gravity analog model. We find that a moderate does of RSV appears to blunt reductions in front and back paw grip force as well as partially protect myofiber cross-sectional area in both the soleus and the gastrocnemius [ 41 ].…”
Section: Future Perspectivesmentioning
confidence: 99%